Analyses of the molecular mechanisms associated with salinity adaption of Trachidermus fasciatus through combined iTRAQ-based proteomics and RNA sequencing-based transcriptomics. (August 2018) - Ma, Qian; Liu, Xinfu; Feng, Wenrong; Liu, Shufang; Zhuang, Zhimeng
Abstract: Osmoregulation mechanism underlying acclimation and adaptation of migratory fish to different salinities has been studied for decades. Recently developed transcriptomic and proteomic techniques would make it possible to provide more reliable data to decipher the mechanism study at a molecular level. Here in this study, an integrative analysis of the kidney-specific transcriptome and proteome was performed to identify important regulators and pathways involved in salinity adaption of roughskin sculpin ( Trachidermus fasciatus ). Fish were subjected to seawater-to-freshwater transfer that was achieved in 24 h, samples were collected at 12, 24 and 48 h after the start of the experiment. Time course profiling of gene and protein expressions were examined using RNA-seq and iTRAQ methods. A total of 1504 differentially expressed genes (DEGs) and 378 differentially expressed proteins (DEPs) were identified at the three time points. 66 proteins were filtered by correlation of transcriptome and proteome results. When comparing the data obtained from the three time points, 12 h exhibited the largest number of DEGs and DEPs, suggesting the time course experiment is critical to clarify the framework of regulatory genes/proteins in response to salinity change. This study provides the first time-course, kidney-specific, combined transcriptomic and proteomic profiling associated with salinity adaption of Trachidermus fasciatus . The results revealed the possibility of T. fasciatus as an experimental animal for osmoregulation studies, showed the powerfulness of combining transcriptomic and proteomic approaches to provide molecular insights of osmoregulation mechanisms in migratory fish.